PERSEPSI PELANGGAN SEPERDUA KOPI SOLO TERHADAP KUALITAS PELAYANAN - Putri, Nesia Margaretta; Hindra H, Nurnawati; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Seperdua Kopi is one of the coffee shops located in Solo City, precisely at JL. Yos Sudarso No. 233, Kratonan, Serengan. Seperdua Kopi has a distinctive coffee taste resulting from a mixture of different coffee beans, such as its mainstay menu